2013
DOI: 10.4315/0362-028x.jfp-12-528
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 5-Log Reduction Times for Escherichia coli O157:H7, Salmonella enterica, or Listeria monocytogenes in Acidified Foods with pH 3.5 or 3.8†

Abstract: A critical factor in ensuring the safety of acidified foods is the establishment of a thermal process that assures the destruction of acid-resistant vegetative pathogenic and spoilage bacteria. For acidified foods such as dressings and mayonnaises with pH values of 3.5 or higher, the high water phase acidity (acetic acid of 1.5 to 2.5% or higher) can contribute to lethality, but there is a lack of data showing how the use of common ingredients such as acetic acid and preservatives, alone or in combination, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…3B). For validation of commercial food manufacturing processes as preventive control steps, a 5-log reduction of a specified pathogen population is often targeted (8,37,38). Microbial reductions of !5 log CFU/g on the injury-recovery media were achieved by 6.0, 5.0, 5.0, and 7.75 min for Salmonella serovars Senftenberg, Newport, and Typhimurium, and for E. faecium, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). For validation of commercial food manufacturing processes as preventive control steps, a 5-log reduction of a specified pathogen population is often targeted (8,37,38). Microbial reductions of !5 log CFU/g on the injury-recovery media were achieved by 6.0, 5.0, 5.0, and 7.75 min for Salmonella serovars Senftenberg, Newport, and Typhimurium, and for E. faecium, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The a w s of the crumb and crust of baked buns were determined separately at 258C, using an AquaLab Series 4TEV a w meter (Decagon Devices, Inc., Pullman, WA). a w s were determined in the first study for pre-and postproof dough, along with separate crumb and crust measurements during baking (2,4,6,8,10,12, and 14 min) and after baking (treatment BþC) buns. At each sampling point, and within 10 s of removal from the oven, the crumb and crust of buns were separated by hand, placed into separate a w cups, sealed with Parafilm M (American National Can Group Inc., Chicago, IL), and analyzed within 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…When Breidt et al (2007) acidified cucumbers with acetic acid (≤ pH 3.3), a 5-log reduction in the E. coli O157:H7 population was achieved after 5.7 and 1.4 days of storage at 10°C and 25°C, respectively. Also, Breidt et al (2013) reported that cucumbers pickled in acetic acid (2.5%) + benzoic acid (0.1%) (pH 3.5) required a minimum of 1.5 days storage at 10°C to achieve a 5-log reduction in the E. coli O157:H7 population. Finally, Lu et al (2013) showed that a mixture of 0.3% fumaric acid (25 mM), 0.06% benzoic acid (5 mM), 0.4% acetic acid (70 mM), and 2% NaCl (pH 3.8) achieved a 5-log CFU/g reduction in the E. coli O157:H7 population after 8.8 days of storage at 10°C, with no change in the sensory attributes of the product.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis was that cultures with superior acid resistance would exhibit long‐term survival desirable for a commercial probiotic refrigerated cucumber pickle product. Cucumber juice medium was used as a generic vegetable broth medium that does not contain known antimicrobial compounds so that the results may be applied to a variety of brined vegetable products (Breidt and others , ).…”
Section: Introductionmentioning
confidence: 99%